The Integration of Individual and Behavioral Factors in Needle Stick Injuries Among Nurses in Hospitals: A Literature Review - Sharfina Ningma Zatalini; Fitria Saftarina; Intan Kusumaningtyas; Winda Trijayanthi Utama (International Journal Of Health Science, 2026)
Needle stick injury (NSI) is one of the most common occupational hazards among nurses and poses a significant risk of transmitting infectious diseases. The occurrence of NSI is influenced by multiple interacting factors, requiring a comprehensive approach to understand these determinants in an integrated manner. This study aimed to analyze the integration of individual and behavioral factors associated with NSI among nurses. The findings indicate that individual factors such as age, education level, and years of service contribute to the basic capacity of nurses in understanding occupational risks. Behavioral factors, including unsafe practices, needle recapping, and non-compliance with standard operating procedures, are the direct causes of NSI. Work environment factors, such as safety training, occupational safety systems, and workload, influence the development of such behaviors. The study concludes that NSI is the result of an interaction between individual, behavioral, and work environment factors, with behavioral factors being the most dominant determinant. Therefore, prevention efforts should be carried out comprehensively by promoting safe behavior supported by a conducive work environment and safety system.